Ativação por laser pulsado da liga TiVNbCr para armazenagem de hidrogênio - Cameirão, Ana Rodrigues (2026)
Multicomponent alloys are a safer and efficient way of storing hydrogen, as they can react reversibly with H to form hydrides. Alloys from the Ti-V-Nb-Cr system, for example, form hydrides capable of storing about 3 wt.% of H. However, when these alloys are exposed to air for long periods, due to surface contamination, it is necessary to perform activation procedures required to restore their hydrogen storage properties. In this context, our group was the pioneer in reporting a new activation method based on the use of a pulsed laser, called PLA (Pulsed Laser Activation). However, the mechanisms involved in laser-matter interaction during the PLA method are not completely understood. Thus, the main objective of this master's project is to investigate the pulsed laser activation (PLA) process of an equiatomic Ti-V-Nb-Cr alloy for hydrogen storage, advancing the understanding of the mechanisms involved in the PLA method. For this purpose, samples of the pure metals and an equiatomic alloy of the Ti-V-Nb-Cr system were prepared under five main conditions and their combinations: 1) pristine, 2) aged in air, 3) aged in water, 4) after thermal activation, and 5) after the PLA method. They were then characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), surface roughness (RA), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), UV-Vis spectroscopy, and a Sieverts-type volumetric apparatus. The results showed that the PLA method was effective as an activation method only for the equiatomic TiVNbCr alloy, promoting high hydrogen capacity and kinetics, reaching 3 wt.% of H in just one minute. Surface analyses also revealed that the PLA method induces surface remelting, increased roughness, the formation of holes and cracks, and the formation of an oxide layer rich in Ti, factors that contribute to the material’s activation.